Integrated control of trypanosomosis - (:unkn) unknown (My University, 2018)
In many parts of Africa, tsetse eradication is impossible due to political, environmental or economic circumstances. In these situations, African animal trypanosomosis control relies on communities or farmer-based control, implemented at a local scale in accordance to the eco-epidemiological context and the cattle rearing system to be sustainable. Management of the African animal trypanosomosis requires integrated controls strategies that combine the use of more than one locally-based tool and where possible, needs to be assisted by veterinarians and other animal health professionals. Several tsetse control methods based on insecticide treated cattle (i.e. pour-on, manual spraying, community bath) and insecticide treated target (traps and screens impregnated with insecticides) are available and should be complemented with diagnostic tests and medication (active trypanocides with prophylactic and/or therapeutic action). However, their adoption is mainly dependent on the engagement of communities, farmers and herders. Indeed, the adoption of a locally-adapted control strategy will depend on farmers socio-technical networks, the cost-effectiveness of the control activities, as well as the time and cost for implementation. In general, insecticide treated cattle methods are the most suitable and acceptable for farmers, because they protect a private good i.e. cattle, whereas insecticide treated targets are generally considered to provide a public good. Nonetheless, selection of the most appropriate tools requires consideration of local disease epidemiology (including host-parasite coevolution), local environmental and socioeconomic constraints. The active involvement of communities, farmers and herders is essential from the beginning of the conception of innovative control strategies, and the cost of local integrated pest management should be reduced as much as possible, to be adopted as an acceptable and sustainable animal production cost.
Keywords: African Research